KAJIAN HUKUM TERHADAP KETENTUAN DAN PROSEDUR PERALIHAN WARIS HAK ATAS TANAH - Putri Intan Ayuningutami; Fatma Ulfatun Najicha (Universitas Sriwijaya, 2021)
Land rights are rights that are mostly owned by Indonesian people. Because land ownership is not a new thing in our society. Because having land rights, problems that will arise in the future are the transfer of land rights, the transfer of land rights in Indonesian society mostly uses the inheritance system. The transfer of inheritance rights to land is a problem that often arises in everyday life today. The transfer of land rights using the inheritance system is a transfer of ownership of a land owned by the heir to the heirs because the heir has died. One of the transfers of land rights is regulated in Law number 5 of 1960 concerning Basic Regulations on Agrarian Principles (UUPA) in Article 21 Paragraph (5). However, the inheritance of land rights through the inheritance system still often causes many problems in the community. Therefore, this paper aims to examine more deeply the provisions and procedures for the transfer of inheritance of land rights in accordance with applicable law in Indonesia. The method in this paper uses a normative legal research method with the aim of further reviewing the provisions and procedures for the transfer of land rights.